Chatbots in Cybersecurity: Enhancing Security Chatbot Efficacy through Iterative Feedback Loops and User-Centric Approaches (American Journal of Innovation in Science and Engineering, 2024)
Chatbots are of continuous importance in our interactive lives. Although used in several domains, there are questions about its security assurance; therefore, there is a need to know its capabilities, limitations, and challenges in cybersecurity. The research explores the use of chatbots in enhancing cyber defences and their potentials. It examines chatbots’ current applications in cybersecurity, including IT services, information protection, and user education. Furthermore, the research proposes implementing an Intelligent Chatbot Security Assistant (ICSA) model on WhatsApp to detect and respond to cyberattacks based on user conversations and identifies the challenges with this implementation. To address these challenges, it suggests incorporating enhanced privacy measures, real-time monitoring, rigorous evaluation and validation, and concludes with user-centric design principles using iterative feedback. This research provides valuable insights into the use of chatbots in cybersecurity, their current level of research and implementation as a cybersecurity tool, and directions for future research.